Sinus Retrospective Analysis of Surgeries in a Hospital School - de Carvalho, Thiago Bittencourt Ottoni; Conrado, Tiago José; Genaro, Tiago L.; Fernandes, Atílio Maximino; Maniglia, José Victor (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The ENT is a medical specialty that covers 4.4% of all doctors in São Paulo, with a variety of surgical procedures distributed between pharynx, nose, ear and larynx. Knowing the profile of a reference service in otolaryngology allows for a better organization, scaling the volume of care and surgeries, providing better training to the student and resident physician.Objective: To describe the profile of sinonasal surgery and patients to them in the department of otolaryngology and head and neck surgery at a teaching hospital.Method: We conducted a cohort study of cross-sectional retrospective study with review of 872 charts of patients undergoing surgery Sinus between January 2006 and December 2008. Used questionnaires, seeking sex, age, surgical diagnosis and surgery.Results: Of 872 patients studied, 45.4% were female and 54.6% male, ranging in an age group 40-80 years (mean 29.8 years). The main surgical diagnoses were: nasal septum deviation (n = 457), nasal deformity after trauma (n = 287), enlarged turbinates (n = 153), rhinosinusal polyposis (n = 73), chronic sinusitis (n = 32). Among the most frequently performed surgical procedures include: septoplasty (n = 388), rhinoplasty (n = 215), FESS (n = 131), intra-turbinal cauterization (n = 114), reconstructive rhinoplasty (n = 73), turbinectomy (n = 43), turbinoplasty (n = 55). It is emphasized that patients may have received more than one surgical diagnosis and realized more than one surgery, depending on the alert.Conclusion: We present the volume and diversity of Sinus surgeries performed in our department, contributing to the scarce scientific literature on this type of case.
Keywords: nose diseases; nose; nose neoplasms; rhinoplasty; otorhinolaryngologic surgical procedures